Identification of risk factors for hypertension in overweight and obese people and analysis of risk factor interactions: an R-based analysis - Li, LuWei; Cheng, SiShuai; Xu, GuoQuan (Frontiers in Cardiovascular Medicine, 2023)
Objective: This study identified the independent risk factors for hypertension in people with overweight and obesity and also analyzed the interaction between the risk factors.Methods: A total of 5098 people with overweight and obesity were enrolled in this study. First, the clinical metabolic characteristics of hypertension and control groups were compared. The logistic regression (LR) and classification and regression trees (CRT)-based decision tree (DT) models were used to screen the independent risk factors for hypertension in people with overweight and obesity. Finally, the receiver operating characteristic (ROC) and calibration curves were used to analyze the accuracy and identification ability of the LR and DT models.Results: Age, UA, FPG, SBP, Cr, AST, TG, and FPG were higher in the hypertension group than in the control group (P < 0.05). The results of LR revealed that NAFLD, FPG, age, TG, LDL-c, UA, and Cr were positively correlated with hypertension in people with overweight and obesity, and GFR was negatively correlated with hypertension in people with overweight and obesity (P < 0.05). The DT model suggested that the risk factors of age, FPG, and UA interacted with each other. The multiplicative single and multiple factor analysis for FPG + UA, age + UA, age + FPG revealed a positive multiplicative interaction (P < 0.05, B ≠ 0, OR > 1). The additive single and multiple factor analysis for age + UA indicated a positive additive interaction. The ROC and calibration curve analysis indicated that the CRT decision tree, FPG + UA, age + UA, and age + FPG have certain accuracy and discrimination ability.The independent risk factors for hypertension in people with overweight and obesity overweight and obese people : overweight and obese people : overweight and obese people : overweight and obese people : overweight and obese people : overweight and obese people :included NAFLD, FPG, age, TG, LDL-c, UA, and Cr. Among these, age + UA exhibited synergistic interaction, thereby providing a reference for the prevention and control of hypertension in people with overweight and obesity.